Implantation of toric intraocular lenses in patients with cataract and keratoconus: a case series - Allard K; Zetterberg M (International Medical Case Reports Journal, 2018)
Karin Allard,1 Madeleine Zetterberg1,2 1Department of Ophthalmology, Sahlgrenska University Hospital, Mölndal, Sweden; 2Department of Clinical Neuroscience/Ophtalmology, Institute of Neuroscience and Physiology, The Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden Purpose: To describe the results of phacoemulsification and implantation of toric intraocular lenses (IOLs) in patients with cataract and keratoconus. Patients and methods: Prospective study of 4 patients (4 eyes) with cataract and keratoconus who underwent phacoemulsification with implantation of a toric IOL. Two different toric IOLs were used: AcrySof IQ SN6AT9 and AT Torbi 709M(P). Corneal tomography was performed preoperatively using Scheimpflug technique with Pentacam. Astigmatism was regular or slightly irregular in all patients. Postoperatively, best-corrected visual acuity (BCVA), astigmatism, spherical equivalent, and complications were recorded for all patients. Follow-up time was between 4 weeks and 7 months. Results: BCVA increased and astigmatism decreased in all patients. BCVA increased from 20/50 to 20/40 in patient 1, from 20/63 to 20/20 in patient 2, from 20/40 to 20/32 in patient 3, and from hand motion to 20/40 in patient 4. Astigmatism decreased from –6.12 to –3.75 D in patient 1, from –4.62 to –1.75 D in patient 2, from –9.0 to –3.0 D in patient 3, and from –8.0 to –2.75 D in patient 4. One patient developed pseudophakic cystoid macular edema, but at last follow-up after 6 months the edema had resolved. Another patient developed posterior capsular opacification after 2 months. No misalignment of the axis of the IOL was observed. Conclusion: Correction of both astigmatism and cataract with phacoemulsification and implantation of a toric IOL can be an effective and safe choice for patients with cataract and keratoconus. However, predicting the refractive outcome in cataract surgery is difficult in patients with keratoconus, and the surgeon should be aware of different sources of biometric errors and the possible consequences. Keywords: keratoconus, cataract, astigmatism, phacoemulsification, toric intraocular lens